Mineralogy and chemical composition of lithic artefacts for characterization of raw materials and provenance in archaeological sites of Salobo, Carajás, Pará, Brazil - Pantoja, Heliana Mendes; da Costa, Marcondes Lima; da Silveira, Maura Imazio; Rodet, Maria Jacqueline; Angélica, Rômulo; Paz, Simone; Rodrigues, Suyanne Flávia Santos (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2017)
The Carajás Mineral Province is home to several archaeological sites, each with numerous stone artefacts elaborated in diferente materials. We studied the morphology, mineralogy, and chemistry of lithic artefacts recovered at the archaeological sites in the impacted area of the Solobo copper and gold mine in the Carajás Mineral Province. The results obtained from XRD, XRF and SEM/EDS analyses show that the starting material used was a semi-hard kaolin (semi-flint) that consisted of kaolinite, cryptocrystalline quartz, florencite, sericite, and hematite. This suggests that the same source of raw materials was involved and that this possibly reflected preference for this material. Additionally, the hardness of this raw material probably allowed the artefacts to be elaborated with ease. The mineralogical and chemical results, combined with characteristics of the artefacts’ morphology and texture, indicate a relation among the archaeological sites. Similar material to that used in the production of the Solobo artefacts was found in the Alto Bonito amethyst mines that are located 40 km to the north. This site is therefore considered as the source of the raw material used for these artefacts. Finally, this indication is supported by the association of the abundant rock crystal chips and amethyst with the semi-hard kaolin present at the Alto Bonito mine.